Tracing the Effects of the Covid-19 Pandemic on Car Usage in Germany - an Analysis of the German Mobility Panel - Ecke, Lisa; Magdolen, Miriam; Chlond, Bastian; Vortisch, Peter (European Journal of Transport and Infrastructure Research, 2021)
Being a vast external influence, the COVID-19 pandemic causes major changes in travel behavior on the individual level. This exceptional situation and the political measures such as the lockdown lead to decreased overall travel demand and shifts in mode choice. To understand these effects, the analysis of car usage in private households offers explanatory insights. To this aim, this study provides a differentiation of car usage before and during the COVID -19 pandemic in spring 2020. Furthermore, insights into structural changes of car usage in private households based on German Mobility Panel data are presented. The results show that during the COVID -19 pandemic car usage was affected, and overall mileage decreased. Especially newer cars with large cubic capacity show a large decrease in mileage by 39 % between 2019 and 2020. In addition, we see that the type of car usage (business/private) and the household characteristics are related to different magnitudes of change in car usage. Overall, it becomes evident that examining identical households and cars before and during the pandemic allows for a deeper understanding of the impacts of the COVID -19 pandemic.